Optimizing treatment selection: outcomes of radical cystectomy in patients eligible for trimodal therapy - Mangold, Maurin Helen; Nientiedt, Malin; Waldbillig, Frank; Michel, Maurice Stephan; Carl, Nicolas; Grüne, Britta; Kriegmair, Maximilian (World journal of urology, 2025)
This study examines oncological and functional outcomes in a subset of patients eligible for trimodal therapy (TMT) within a large radical cystectomy (RC) cohort. It aims to determine whether TMT should be offered to all eligible patients, rather than exclusively to patients with significant comorbidities who are at high perioperative risk.